Prihodnjik - čas ali naklon? - Pallasová, Eva (Slavistična revija, 1998)
The Old Church Slavonic texts give very significant evidence of the development of the analytic future tense in the Slavonic languages. The texts manifest quite clear that the Old Church Slavonic belongs to the South Slavonic linguistic territory. The periphrastic future forms are built up of the deontic modal expressions anf of an expressions signifying the interntional state of will. Such forms represent the first stage of the later development process which can be characterised by voiding of the original modal expressions and transforming them into grammatical particles of the follownig analytical future tense in the South Slavonic languages. During the later estabilshing of the Balkan "linguistic union" (Sprachbund) the process had been undoubtedly supported by the analogical tendencies in the Non-Slavonic languages, in Greek in particular.
Keywords: južnoslovanski jeziki; naklon; prihodnji čas; slovanski jeziki; stara cerkvena slovanščina